Analyzing single-subject design data using statistical process control charts. - Orme, John G.; Cox, Mary Ellen (Social Work Research, 2001)
Part of a special issue on practice and intervention in social work. The writers examine the use of single subject design data in practice evaluation. They discuss in particular the use of statistical process control charts, which are used to detect systematic changes in manufacturing processes; the exhibition of variability in samples, whether in manufacturing products or social work outcomes; potential social work applications; and various control charts.